Harvesting strategies of fuelwood and kraalwood users at Machibi : identifying the driving factors and feedbacks - Scheepers, Kelly (Rhodes University, Faculty of Science, Department of Environmental Science, 2008)
Forest and woodland ecosystems provide a variety of natural resources such as fuelwood, brushwood and kraal posts to local communities, as well as possess important cultural and spiritual value. However, many forests and woodlands worldwide have been unsustainably used and managed. Thus, under pressure from the international conservation community to recognise the importance of people's relationships with their surrounding natural environment, particularly for the natural resources it can provide, and given a move away from the management of forests and woodlands for sustained yields, and according to simple cause and effect models, in favour of systems approaches, South Africa has developed some of the most progressive natural resource management policies in the world. Nevertheless, for these policies to be sensitive to local contexts, there remains a need for a better understanding of how local people in different contexts, determine forest and woodland ecosystems to be of use to them, and what 'usefulness' means to different groups of resources users. This is a case study, which examines the role of fuelwood, brushwood and kraal posts in the rural livelihoods of the people of Machibi village, located in the Eastern Cape province of South Africa, through people's preferences for particular landscapes and species, accessed for these purposes, and the trade-offs people make between resource availability and resource accessibility. Key objectives of the study are to 1) determine the preferred landscapes and species for fuelwood, brushwood and kraal posts at Machibi, 2) determine the landscapes and species actually used for fuelwood, brushwood and kraal posts, and 3) with the help of a conceptual model, and using iterative modelling as a tool, determine the factors that influence people's harvesting strategies in terms of the costs and benefits associated with the different landscape and species options. On the basis of this knowledge, the study provides some guiding principles for the better use and management of these landscapes and species for fuelwood, brushwood and kraal posts. An innovative research approach and methodology that integrates social and ecological systems, works across disciplines, and draws on different types of knowledge is used to develop and test a conceptual model of the harvesting strategies of fuelwood and kraalwood users at Machibi. Participatory methods such as workshops, participatory resource mapping, ranking exercises and trend-lines were used to tap into local knowledge while plotless vegetation sampling and GIS maps were used to capture the scientific information. Results showed that people did not always use the landscapes and species they preferred. However, the local people did behave in a rational manner by weighing up the returns from harvesting and accessibility costs associated with the respective options available to them, before selecting the option(s) associated with the greatest net benefits. At the landscape level, people made trade-offs between the returns from harvesting and the accessibility costs of using particular landscapes in addition to costs associated with the physical work of harvesting fuelwood, brushwood or kraal posts from these landscapes. At the species level, people made trade-offs between the returns from harvesting and the accessibility costs of harvesting particular species for fuelwood, brushwood and kraal posts, or the costs of commercial alternatives. Costbenefit factors that influenced people's resource use patterns also differed across landscapes and species for fuelwood, brushwood and kraal posts, respectively. Consequently, a range of diverse and flexible management options and strategies is recommended for the wise use and management of these landscapes and species, focused on short, medium and long term goals. These strategies examine the use of cost - benefit incentives to influence people's landscape and species use patterns.
Keywords: Fuelwood -- South Africa -- Eastern Cape; Forest ecology -- South Africa -- Eastern; Cape Natural resources -- South Africa -- Eastern Cape; Natural resources -- Management -- South Africa -- Eastern Cape; Conservation of natural resources -- South Africa -- Eastern Cape; Landscape protection -- Economic aspects -- South Africa -- Eastern Cape; Fuelwood consumption -- South Africa -- Eastern Cape; Fuelwood consumption -- Economic aspects -- South Africa -- Eastern Cape; Forests and forestry -- South Africa -- Eastern Cape; Fuelwood conservation -- South Africa -- Eastern Cape